2019
DOI: 10.3390/jfmk4030047
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of an Energy Drink on Psychomotor Vigilance in Trained Individuals

Abstract: The psychomotor vigilance test (PVT) measures one’s behavioral alertness. It is a visual test that involves measuring the speed at which a person reacts to visual stimuli over a fixed time frame (e.g., 5 min). The purpose of this study was to assess the effects of an energy drink on psychomotor vigilance as well as a simple measure of muscular endurance (i.e., push-ups). A total of 20 exercise-trained men (n = 11) and women (n = 9) (mean SD: age 32 7 years; height 169 10 cm; weight; 74.5 14.5 kg; percent body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…However, it is important to note that the majority of the acute performance and metabolic benefits of energy drinks appear to be mediated by their caffeine and/or carbohydrate content [4]. To date, several investigations have assessed the efficacy of energy drinks and related products to improve muscular strength and power [5,6], muscular endurance [7], behavioral alertness [8], and sport-specific performance [9], with generally-positive results [10]. In some cases, researchers are faced with significant challenges when attempting to quantify the ergogenic potential of a given energy product, as energy drink labels will often list many ingredients in "proprietary blends," with exact amounts not provided [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to note that the majority of the acute performance and metabolic benefits of energy drinks appear to be mediated by their caffeine and/or carbohydrate content [4]. To date, several investigations have assessed the efficacy of energy drinks and related products to improve muscular strength and power [5,6], muscular endurance [7], behavioral alertness [8], and sport-specific performance [9], with generally-positive results [10]. In some cases, researchers are faced with significant challenges when attempting to quantify the ergogenic potential of a given energy product, as energy drink labels will often list many ingredients in "proprietary blends," with exact amounts not provided [4].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies assessed the effect of caffeine on the improvement of cognitive functions and marksmanship effectiveness in soldiers 13 , 17 , 18 . Whereas, DeVocht et al 19 studied the impact of a chiropractic manipulation session on the reaction speed in special unit soldiers.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the researchers found that the smallest dose resulted in the greatest improvements in reaction time performance compared to placebo, though the other two doses were still beneficial. A study conducted by Concerto and colleagues [ 199 ] also found similar results using a sugar-free formulation of the same product, which was further supported by two studies that utilized ED ingredients in isolation [ 200 , 201 ]. In a more recent study, Evans et al [ 202 ] found improvements in Pattern Comparison Processing Speed as well as a lower number of false starts during a Psychomotor Vigilance Test following acute consumption of an ED containing 300 mg of caffeine.…”
Section: Reaction Timementioning
confidence: 55%
“…Chtourou and colleagues [ 146 ] demonstrated that consumption of an ED containing approximately 1 mg∙kg BW −1 caffeine could positively affect aspects of mood, finding significant reductions in self-reported measures of confusion, fatigue, anger, and anxiety as well as significant improvements in self-reported vigor. Seidl et al [ 200 ] also investigated the same product formulation in college-aged graduate students, reporting that feelings of well-being, vitality, and social extraversion were maintained after consumption of the ED but not placebo. Duncan et al [ 154 ] likewise noted that athletes who consumed an ED reported significantly greater readiness to invest mental effort.…”
Section: Subjective Effectsmentioning
confidence: 99%